Trends in adolescent first births in sub-Saharan Africa: a tale of increasing inequity? - Sarah Neal; Andrew Amos Channon; Venkatraman Chandra-Mouli; Nyovani Madise (BMC, 2020)
Abstract Background Single aggregate figures for adolescent pregnancy may fail to demonstrate particular population groups where rates are very high, or where progress has been slow. In addition, most indicators fail to separate younger from older adolescents. As there is some evidence that the disadvantages faced by adolescent mothers are greatest for those at the younger end of the spectrum, this is an important omission. This paper provides information on levels and trends of adolescent first births in 22 countries (at national and regional level) disaggregated by age (< 16 years, 16/17 years and 18/19 years), socio-economic status and place of residence. It highlights differences and similarities between countries in the characteristics of women who experience first birth during adolescence, as well as providing information on trends to identify groups where progress in reducing adolescent first births is poor. Methodology In this descriptive and trend analysis study we used data from 22 low- and middle-income countries from sub-Saharan Africa that have at least three Demographic and Health Surveys (DHS) since 1990, with the most recent carried out after 2005. Adolescent first births from the most recent survey are analysed by age, wealth, and residence by country and region for women aged 20-24 years at time of survey. We also calculated annual percentage rates of change (using both short- and longer-term data) for adolescent first births disaggregated by age, family wealth and residence and examined changes in concentration indices (CI). Findings Overall percentages of adolescent first births vary considerably between countries for all disaggregated age groups. The burden of first birth among adolescents is significant, including in the youngest age group: in some countries over 20% of women gave birth before 16 years of age (e.g. Mali and Niger). Adolescent first births are more common among women who are poorer, and live in rural areas; early adolescent first births before 16 years of age are particularly concentrated in these disadvantaged groups. Progress in reducing adolescent first births has also been particularly poor amongst these vulnerable groups, leading to increasing inequity. Conclusions Findings from this study show that adolescent births are concentrated among vulnerable groups where progress is often poorest. Strategies and programmes need to be developed to reduce adolescent pregnancies in marginalised young women in low- and middle-income countries.